OPTIMALISASI PERAN PEMERINTAH DAERAH DALAM PERLINDUNGAN HUKUM TERHADAP BERAS BERDASARKAN KONSEP KEDAULATAN PANGAN DI INDONESIA (Universitas Suryakancana, 2019)
As a staple food in Indonesia, the availability of rice are needed to continue until whenever. Because agriculture is still the source of livelihood of the majority of the workforce in Indonesia. Hence the presence of the government is necessary, governments can differentiate into central government and local governments. In UUD 1945 Pasal 18A ayat (1) mentions the relationship of authority between the central government and provincial government, counties, and cities, or between provinces and districts and cities, regulated by law with due regard to the specificity and diversity of the area. Regional autonomy is one manifestation of freedom for the regions to be involved in designing the activity of politics and government at the local level in order to strengthen the power of national government. Thus the role of local government is very important to the affairs of the availability of rice in the presence of local autonomy. The local government and regional autonomy can be free to design a territory in support of the central government towards food security.Undang-Undang No. 18 tahun 2012 tentang Pangan mentions the issue of food intended to achieve three things at once, namely food sovereignty, food self-sufficiency and food security. President Jokowi that: